Factors affecting House Sparrow "Passer domesticus" distribution in the Kannur district of Kerala, India - Bijith, Puthiyaveettil; Roshnath, Ramesh (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
House Sparrows are urban birds which are thought to be declining in differnt countires. The House Sparrow population in the Kannur district of Kerala in India was studiem from March to May 2021 to understand the change in population and to identify the habitat variables that predict their distribution. A total of 914 House Sparrows were recorded from 61 sites. Compared with a previous study, the overall House Sparrow population declined by 27%. The sites having ration, grocery and chicken shops were found to have good House Sparrow populations. The presence or absence of roosting trees, old buildings, agricultural areas, and mobile towers didn`t affect House Sparrow populations.
Keywords: House Sparrows; population; habitat; decline; Urban-semi urban-rural region